Effect of resected lung lobe on the prediction of postoperative pulmonary function. (28th September 2022) - Shibazaki, Takamasa; Mori, Shohei; Noda, Yuki; Tsukamoto, Yo; Kato, Daiki; Nakada, Takeo; Yabe, Mitsuo; Matsudaira, Hideki; Hirano, Jun; Ohtsuka, Takashi
Abstract: OBJECTIVES: This study examined whether a resected lung lobe can affect the accuracy of postoperative forced expiratory volume in 1 s (FEV1) predicted using the subsegment counting method and three-dimensional computed tomography (3D-CT) volumetry. METHODS: Overall, 125 patients who underwent lobectomy through video-assisted thoracic surgery were enrolled in this retrospective study. Pulmonary function tests were performed preoperatively and postoperatively at 3 months. We defined the accuracy index as the ratio of predicted postoperative FEV1 to measured postoperative FEV1 and compared the accuracy index of the subsegment counting method and 3D-CT volumetry. Factors affecting the accuracy index were also examined. RESULTS: The accuracy index of the subsegment counting method was 0.94 ± 0.12, versus 0.93 ± 0.11 for 3D-CT volumetry ( P = 0.539). There was a significant difference among the resected lobes in the accuracy index of the subsegment counting method ( P < 0.001) but not in that of 3D-CT volumetry ( P = 0.370). The resected lobe, the number of staples used for interlobar dissection and interstitial pneumonia were significantly associated with the accuracy index of the subsegment counting method (all P < 0.001). The number of staples and interstitial pneumonia were significantly associated with the accuracy index of 3D-CT volumetry ( P < 0.001, respectively), whereas the resected lobe was not a significant factor ( P = 0.240). CONCLUSIONS: The resected lobe affected the accuracy of the subsegment counting method but not that of 3D-CT volumetry. Furthermore, 3D-CT volumetry predicted postoperative FEV1 independent of the resected lobe. Abstract : The accurate prediction of postoperative forced expiratory volume in 1 s (FEV1) is important for estimating the risk for postoperative complications and long-term disability [1, 2].